AIDS Presenting as Granulomatous Amebic Encephalitis: PET and MR Imaging correlation. Issue 6 (10th February 2015) - Dowell, Joshua D.; Mukherjee, Sugoto; Raghavan, Prashant; Rehm, Patrice K.
ABSTRACT Granulomatous amebic encephalitis (GAE) is a rare and oftentimes fatal disease in immune compromised patients caused by free living amebae Acanthamoeba and Balamuthia. We report a patient in whom GAE secondary to Acanthamoeba was the initial presentation of acquired immunodeficiency syndrome in a 41‐year‐old male, and discuss the FDG positron emission tomography (PET) and magnetic resonance imaging findings that preceded the pathological diagnosis. The PET results provided complementary information when coupled with the MR brain findings. Improved understanding of the clinical and imaging findings of this deadly disease is the best hope for early diagnosis and treatment of this uncommon but deadly disease.